Penerapaan Model Pembelajaran Kooperatif Tipe STAD Sebagai Upaya Meningkatkan Hasil Belajar Matematika Peserta Didik pada Materi Lingkaran di Kelas VI SDN 30/X Kampung Laut T.A 2021/2022 - Hasnah Hasnah (Journal on Education, 2022)
This study aims to describe and obtain information on improving learning outcomes of mathematics content through the STAD type cooperative learning model. This research is classroom action research consisting of two cycles, each cycle consisting of two meetings. Each meeting consists of four stages, namely planning, implementation, observation, and reflection. The subjects of this study were students of class VI SDN 30/X Kampung Laut, totaling 21 people. This research was conducted in the odd semester of the 2021/2022 academic year. Data collection techniques using tests, observations, and documentation. Data were analyzed using percentages. The results of the research show that through the STAD type cooperative learning model can improve the mathematics learning outcomes of sixth grade students at SDN 30/X Kampung Laut by giving rewards.